The Presence of the Field of Geodesy and Cartography Today - Inomova Nargiza Rustamovna (Genius Journals, 2023)
The article contains information about the history of the development of the field of geodesy and cartography and its current status, as well as the methods of expressing the difference between the Geoid and the Earth's ellipsoid.
Keywords: Cartography; gravity; geodesy; topography